Neuropeptide S Counteracts Paradoxical Sleep Deprivation-Induced Anxiety-Like Behavior and Sleep Disturbances - Xie, Jun-Fan; Shao, Yu-Feng; Wang, Hai-Liang; Wang, Can; Cui, Guang-Fu; Kong, Xiang-Pan; Wang, Lin-Xin; Chen, Yu-Nong; Cong, Chao-Yu; Chen, Hai-Lin; Hou, Yi-Ping (Frontiers in Cellular Neuroscience, 2018)
Reply：We appreciate the constructive suggestions of the reviewer. As the reviewer suggested, PSD + Sal and PSD + NPS groups and two-way ANOVA analysis have been carried out in Fos counting and co-expression of Fos and NPSR neurons in the amygdala. The new Fig. 1, Fig. 7 and 8 have been modified. The corresponding descriptions to adding experimental groups have been presented in MATERIALS AND METHODS, RESULTS and DISCUSSION of this revised manuscript.